Penerapan Manajemen Kualitas Terhadap Kinerja Mandor Pada Proyek Apartemen - Moch Muzaki; Felicia T. Nuciferani (Borneo Engineering : Jurnal Teknik Sipil, 2020)
The Embodiment of construction quality can be achieved by implementing quality management, one of the workforce used in implementing quality management is the foreman. A construction company has standards or guidelines for implementing quality management that must be carried out by the foreman. This study will discuss the relationship between the level of the foreman's ability and the influence of the foreman's ability on the application of quality management. Qualitative descriptive method is done by distributing questionnaires followed by validity, reliability, t-test, F-test, and classical assumption test. The results showed a simultaneous test for educational variables, work experience, motivation, and discipline influenced the ability of the foreman in implementing quality management of 2,510. The partial test shows that the work experience variable influences the foreman's ability to implement quality management by 2,178. So that the test results obtained for the regression model that is Y = 36,130 + 1,353X2 + ei, that work experience have a very dominant influence on the ability of the foreman in implementing quality management in Surabaya apartment building construction projects.